(untitled) (CIPEEX, 2022)
MENTAL STRESS REFERS TO THE BODY’S RESPONSES TO SITUATIONS THAT DISTURB THE BODY’S HOMEOSTASIS AND, THUS, INFLUENCES THE VARIOUS SYSTEMS OF THE BODY, INCLUDING THE CARDIOVASCULAR SYSTEM, WHICH WILL BE ADDRESSED IN THIS STUDY. THE METHODOLOGY WAS BASED ON THE PECO STRATEGY, USING ARTICLES FOUND IN THE PUBMED DATABASE, BASED ON INCLUSION CRITERIA THAT INVOLVED RESEARCH THAT HAD AS A POPULATION MEN AND WOMEN AGED BETWEEN 18 AND 59 YEARS, WHICH USED AS SOME METHOD OF ANALYSIS TO MENTAL STRESS. OUTCOME VARIABLES WERE ASSESSMENT OF HEART RATE, SYSTEMIC BLOOD PRESSURE, ELECTROCARDIOGRAMS AND CARDIAC OUTPUT. WITH THE ANALYSIS OF THESE STUDIES, IT WAS POSSIBLE TO OBSERVE AN INCREASE IN SYSTOLIC AND DIASTOLIC BLOOD PRESSURE AND HEART RATE DURING PERIODS OF STRESS. IN ADDITION, IT WAS EXPOSED THAT THERE IS A HABITUATION OF THE CARDIOVASCULAR SYSTEM TO STRESS, THAT IS, WHEN THE SAME STRESSFUL ACTIVITY IS REPEATED, THE BODY IS ABLE TO REACT IN A LESS EXCESSIVE WAY WHEN COMPARED TO THE FIRST SITUATION. FINALLY, IT WAS CONCLUDED THAT THERE IS AN INCREASE IN CARDIAC PARAMETERS AFTER STRESSFUL SITUATIONS, IN ADDITION TO THEIR ABILITY TO HABITUATE AFTER THE APPLIED TESTS.